2017
DOI: 10.1108/mrr-04-2016-0092
|View full text |Cite
|
Sign up to set email alerts
|

Consumer evaluation of ingredient branding strategy

Abstract: Purpose Prior research in ingredient branding (IB) has identified several important decision variables consumers use when evaluating IB alliances. This exploratory research aims to investigate the relationship between these variables and consumers’ buying likelihood of the IB alliance and the relative importance of these variables for low- vs high-involvement product categories. Design/methodology/approach A study with the participation of 458 mTurkers was conducted and the data were analyzed using random fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 65 publications
(72 reference statements)
0
15
0
Order By: Relevance
“…It is accepted that an individual’s behaviour intentions do not always translate into real behaviours. Therefore, collecting actual field data would contribute to the understanding of co‐branding success and offer practical implications (Dalman & Puranam, 2017; Nisbett & Wilson, 1977). Although the use of cross‐sectional data is understandable due to limited resources, it does not allow for a change in attitude towards co‐branding over different stages of its life cycle to be taken into account.…”
Section: Future Research Directionsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is accepted that an individual’s behaviour intentions do not always translate into real behaviours. Therefore, collecting actual field data would contribute to the understanding of co‐branding success and offer practical implications (Dalman & Puranam, 2017; Nisbett & Wilson, 1977). Although the use of cross‐sectional data is understandable due to limited resources, it does not allow for a change in attitude towards co‐branding over different stages of its life cycle to be taken into account.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…On the other hand, Bouten et al (2011) showed that product fit, brand fit, and pre‐attitude towards brands all had a significant positive impact on the evaluation of co‐branding, but that brand familiarity did not. While co‐branding has been extensively studied in the last 20 years, there has been no research aggregating all the relevant studies on success drivers (Dalman & Puranam, 2017; Helmig et al, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations